Quantification of nanoparticle concentration in colloidal suspensions by a non-destructive optical method. (26th October 2017) - Clement, Sandhya; Gardner, Brint; Razali, Wan Aizuddin W; Coleman, Victoria A; Jämting, Åsa K; Catchpoole, Heather J; Goldys, Ewa M; Herrmann, Jan; Zvyagin, Andrei
Abstract: The estimation of nanoparticle number concentration in colloidal suspensions is a prerequisite in many procedures, and in particular in multi-stage, low-yield reactions. Here, we describe a rapid, non-destructive method based on optical extinction and dynamic light scattering (DLS), which combines measurements using common bench-top instrumentation with a numerical algorithm to calculate the particle size distribution (PSD) and concentration. These quantities were derived from Mie theory applied to measurements of the optical extinction spectrum of homogeneous, non-absorbing nanoparticles, and the relative PSD of a colloidal suspension. The work presents an approach to account for PSDs achieved by DLS which, due to the underlying model, may not be representative of the true sample PSD. The presented approach estimates the absolute particle number concentration of samples with mono-, bi-modal and broad size distributions with <50% precision. This provides a convenient and practical solution for number concentration estimation required during many applications of colloidal nanomaterials.